The Role of Project-Based Learning in Developing 21st Century Skills - Evaristus Silitubun; Bruna Costa; Zain Nizam (International Journal of Educational Narratives, 2024)
Background: In recent years, the need for 21st-century skills such as critical thinking, collaboration, and creativity has become increasingly significant. Traditional education models often fall short in developing these competencies, making innovative teaching methods like Project-Based Learning (PBL) an important focus in modern educational research. PBL, with its emphasis on real-world problems and student-centered learning, has been seen as a promising approach to cultivate these essential skills. Objectives: This study aims to investigate the role of Project-Based Learning (PBL) in fostering the development of 21st-century skills among students. Method: A mixed-method approach was employed, utilizing both qualitative and quantitative data. Surveys and interviews were conducted with students and educators from various educational institutions that implemented PBL strategies in their curricula. The collected data were analyzed to identify the impacts of PBL on students’ skill development. Results: The findings revealed that PBL significantly contributes to the enhancement of key 21st-century skills. Students demonstrated improved problem-solving abilities, teamwork, communication, and creativity. Moreover, educators observed an increase in student engagement and motivation. Conclusion: Project-Based Learning is an effective pedagogical approach in fostering 21st-century skills. Its emphasis on real-world problem solving and collaborative work provides students with the necessary tools to thrive in an increasingly complex and dynamic world.